Operationalizing the RE-AIM framework to evaluate complex interventions: Lessons learned from the Integrated Research on Acute Malnutrition (IRAM) study - Huybregts, Lieven; Diatta, Ampa Dogui; Diop, Loty; Touré, Mariama; Fall, Talla; Becquey, Elodie (International Food Policy Research Institute, 2023)
The use of theories, models and evaluation frameworks to design and evaluate interventions has now taken center stage in implementation science. The RE-AIM framework is one of the most used frameworks to plan and evaluate the implementation of interventions. RE-AIM framework is not only useful for researchers but also allows program implementers to broaden and structure their analysis to strengthen program implementation, design a performant monitoring and evaluation framework or conduct implementation research. The framework’s key dimensions are reach and effectiveness (at an individual level), adoption and implementation (at actor, staff, system, or policy/other levels), and maintenance (both at individual and actor/staff/system/policy levels) (Box 1). The utilization of the RE-AIM framework is not limited to assessing if a program reaches satisfactory levels of each dimension, but also aims at understanding the barriers and facilitating factors of each dimension. Furthermore, it recommends identifying which subgroups of actors or settings demonstrate good or poor adoption and implementation and to assess which subgroups of program beneficiaries benefit most from good intervention reach and effectiveness. Whereas most experience with RE-AIM comes from public health and behavioral studies conducted in high-income countries, the framework has been increasingly used for programs and interventions implemented in low-and middle-income countries and in a variety of thematic fields. Furthermore, the framework has been extensively used to assess the implementation of interventions consisting of few components. For the assessment of multi-component interventions, one way of applying RE-AIM to is first decompose the multi-components intervention into single components or activities and evaluate every component separately. However, such complex interventions can consist of intervention components or services that are either sequenced, layered, or integrated which may require an extension of the existing RE-AIM framework to evaluate the interaction between intervention components or services. This technical brief provides an example on how RE-AIM was operationalized by the Integrated Research on Acute Malnutrition (IRAM) which assessed the implementation and impact of a complex intervention package. The IRAM intervention aimed at strengthening various services along the continuum of care of child wasting in Mali. IRAM defined the continuum of care of child wasting as a series of services offered by different providers at various levels of care (household, community, facility) that cover the prevention of wasting, the screening for wasting, the referral of cases to treatment services, the admission and treatment of cases, and the post-treatment follow-up and prevention of relapse. We first show how REAIM was applied on single IRAM intervention components and services. We then highlight a few limitations that we encountered with RE-AIM for a complex intervention package and propose how to extend RE-AIM for interventions or services that are sequenced, layered, or integrated.